2006
DOI: 10.1097/01.mlr.0000220833.89050.ed
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization and Outcomes After Bariatric Surgery

Abstract: In contrast to current bariatric studies, which report a 20% in-hospital complication rate, we find a significantly higher complication rate over the 6 months after surgery, resulting in costly readmissions and emergency room visits. Thus, a clear way to reduce the costs and improve outcomes of bariatric surgery is to address the high rate of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 14 publications
7
103
1
2
Order By: Relevance
“…The same occurred in the three-year follow-up cohort of Zingmond et al 21 and the studies by Encinosa et al 22 Our findings confirm that, at least over the short term, from the payer's point of view, the costs do not diminish after surgery; instead, they tend to increase. As expected, the costs in the subgroup with any type of complication after bariatric surgery or a gastrointestinal tract procedure were much higher than among those with uncomplicated procedures.…”
Section: Discussionsupporting
confidence: 79%
“…The same occurred in the three-year follow-up cohort of Zingmond et al 21 and the studies by Encinosa et al 22 Our findings confirm that, at least over the short term, from the payer's point of view, the costs do not diminish after surgery; instead, they tend to increase. As expected, the costs in the subgroup with any type of complication after bariatric surgery or a gastrointestinal tract procedure were much higher than among those with uncomplicated procedures.…”
Section: Discussionsupporting
confidence: 79%
“…Some recent studies have reported that Roux-en-Y (R-Y) gastric bypass, known as bariatric surgery, sometimes caused postoperative hyperoxaluria and subsequent oxalate nephrolithiasis in obese patients [1]. This metabolic abnormality sometimes leads to the development not only of macroscopic renal stones but also of microscopic renal calculi, and results in irreversible renal failure in some patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although complication rates with bariatric surgery when patients are in hospital are high (~20%), a study in the US reported significantly higher complication rates over the 6 months following surgery, resulting in costly readmissions and emergency room visits. 31 Furthermore, Encinosa et al 31 reported that the rate of readmission of bariatric patients increases 64.5% between 30 and 180 days after surgery. It is plausible that after cancellation of health insurance, private patients require access to public services for treatment and revision/reversal.…”
Section: Discussionmentioning
confidence: 99%